Computational molecular evolution - Yang, Ziheng (Oxford : Oxford University Press, 2006)
Covering the modern statistical and computational methods used in molecular evolutionary analysis, such as maximum likelihood and Bayesian statistics, this book is useful for students and professional researchers in the fields of molecular phylogenetics, population genetics, mathematics, statistics and computer science.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Molecular evolution -- Mathematical models; Molecular evolution -- Data processing